2011
DOI: 10.1063/1.3633955
|View full text |Cite
|
Sign up to set email alerts
|

Etched multimode microfiber knot-type loop interferometer refractive index sensor

Abstract: We propose a novel refractive index sensor based on multimode microfiber knot-type loop (NL) interferometer. The middle portion (~5 cm) of a 15 cm long multimode fiber is etched in 48% hydrofluoric acid to reduce its diameter to ~12 μm. A NL of diameter <1 mm is made from the etched fiber. The ends of etched fiber are spliced with single-mode fibers for launching and detecting light from the NL interferometer. The NL introduces path differences to produce interferometric spectra with free spectral range ~16 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Pal et al first etched multimode optical fibers with hydrofluoric acid to generate knot resonators and excite interferometric spectra for refractive index measurements, observing a maximum sensitivity of 172 nm RIU −1 (refractive index unit). [100] However, the microfibers produced by this method often have poor surface quality, which can cause large optical losses. To protect the ultrafine fibers from mechanical effects and to maintain a large evanescent field, Li et al proposed a dip-coating technique, [101] where MKR is first immersed in Teflon solution, then quickly raised and dried to generate a thin and uniform film on its surface.…”
Section: Refractive Index Sensingmentioning
confidence: 99%
“…Pal et al first etched multimode optical fibers with hydrofluoric acid to generate knot resonators and excite interferometric spectra for refractive index measurements, observing a maximum sensitivity of 172 nm RIU −1 (refractive index unit). [100] However, the microfibers produced by this method often have poor surface quality, which can cause large optical losses. To protect the ultrafine fibers from mechanical effects and to maintain a large evanescent field, Li et al proposed a dip-coating technique, [101] where MKR is first immersed in Teflon solution, then quickly raised and dried to generate a thin and uniform film on its surface.…”
Section: Refractive Index Sensingmentioning
confidence: 99%
“…To enhance the mechanical stability of free-standing MNF ring resonators without substrates, in 2006, Jiang et al tied a free-standing MNF into a knot [ 114 ], in which the knot structure was maintained by the friction of the microfibre at the joint area under the tension of the elastically bent knot, and was proved highly stable in water with Q factors up to 31,000 and finesse of 13. Based on MNF knot resonators, a variety of sensing structures have been reported [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. For example, in 2009, Wu et al demonstrated a micro-electromechanical system (MEMS) based optical accelerometer combined with a 386-μm-diameter knot resonator fabricated by a 1.1-μm-diameter silica MNF [ 115 ].…”
Section: Mnf Optical Sensorsmentioning
confidence: 99%
“…The experimental results showed that the microfiber accelerometer had a sensitivity of 654.7 mV/g, with a dynamic range of 20 g. In 2011, using a copper-wire-wrapped microfiber knot resonator (Figure 12), Lim et al demonstrated tuning the resonant wavelength of the microfiber resonator by applying electric current to the copper wire [68], and realized a compact current sensor with the maximum tuning slope of 51.3 pm/A 2 . Besides the above-mentioned examples, microfiber-knot-based optical sensors have also been reported for measurement of refractive index [64,69], humidity [61,70], temperature [57,69,71,72], and magnetic field [73]. Overall, as a free-standing microfiber cavity without the supporting substrate, the microfiber knot resonator offers opportunities for optical sensing with high sensitivity, fast response, high robustness and compact size in liquid and/or vibrating environment.…”
Section: Microfiber Functionalized Structures and Optical Sensorsmentioning
confidence: 99%